Lifetime history of indoor tanning in young people: a retrospective assessment of initiation, persistence, and correlates - Lostritto Karen; Ferrucci Leah M; Cartmel Brenda; Leffell David J; Molinaro Annette M; Bale Allen E; Mayne Susan T (BMC, 2012)
Abstract Background Despite educational and public health campaigns to convey the risks of indoor tanning, many individuals around the world continue to engage in this behavior. Few descriptive studies of indoor tanning have collected information pertaining to the lifetime history of indoor tanning, thereby limiting our ability to understand indoor tanning patterns and potentially target interventions for individuals who not only initiate, but continue to persistently engage in indoor tanning. Methods In-person interviews elicited detailed retrospective information on lifetime history of indoor tanning among white individuals (n = 401) under age 40 seen by a dermatologist for a minor benign skin condition. These individuals were controls in a case-control study of early-onset basal cell carcinoma. Outcomes of interest included ever indoor tanning in both males and females, as well as persistent indoor tanning in females - defined as females over age 31 who tanned indoors at least once in the last three or all four of four specified age periods (ages 11-15, 16-20, 21-30 and 31 or older). Multivariate logistic regression was used to identify sociodemographic and lifestyle correlates of ever and persistent indoor tanning in females. Results Approximately three-quarters (73.3%) of females and 38.3% of males ever tanned indoors, with a median age of initiation of 17.0 and 21.5, respectively. Among indoor tanners, 39.3% of females and 21.7% of males reported being burned while indoor tanning. Female ever indoor tanners were younger, had darker color eyes, and sunbathed more frequently than females who never tanned indoors. Using unique lifetime exposure data, 24.7% of female indoor tanners 31 and older persistently tanned indoors starting as teenagers. Female persistent indoor tanners drank significantly more alcohol, were less educated, had skin that tanned with prolonged sun exposure, and sunbathed outdoors more frequently than non-persistent tanners. Conclusions Indoor tanning was strikingly common in this population, especially among females. Persistent indoor tanners had other high-risk behaviors (alcohol, sunbathing), suggesting that multi-faceted behavioral interventions aimed at health promotion/disease prevention may be needed in this population.